Anak Jalanan Dalam Konstelasi Hukum Indonesia - Zulkifli, Zulkifli; Luthfiyah, Zeni; Umar, Mustofa; Winarni, Harti; Arifin, Zainul; Rahayu, Supriati H (Universitas Cokroaminoto Yogyakarta, 2023)
Identification of various laws in Indonesia that provide legal protection to street children in carrying out their rights and obligations as part of Indonesian citizens. This legal inventory resulted in the finding that legally they have become the attention of the state legally so that they deserve proper legal protection for children as usual. Such research is useful in strengthening the role and authority of institutions or related parties when dealing with street children in order to maintain and even improve their welfare.